Analysis and Control of Chaotic DC-DC Switching Power Converters - Rodríguez Marrero, José Luis (Sin editorial (Orlando, Estados Unidos de América), 2002)
In this paper we review our approach to computing the static characteristics-such as voltage gain and average switching frequency-of open loop DC-DC converters under current-mode control in the chaotic regime. Linearized averaged models that govern the dynamics of the converter are presented and used to design feedback controllers. Initial results of experiments with a real boost converter operating in the chaotic regime are shown, and compare favorably with our calculations and simulations.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)